A implementação da política estadual de prevenção social à criminalidade de Minas Gerais: paradigmas, coalizões e incrementalismo - Souza, Talles Andrade de (2016)
This study analyses the implementation process of Minas Gerais State Policy to Social Crime Prevention within the institutional framework of Minas Gerais state government’s Secretary for Social Defense during the period of 2003 to 2014. This study approached paradigms that support public policies on security, framing the main values and world visions that guide traditional practices in the field of public security. It has been introduced a possibility of change through the paradigm of Citizen Security, which has brought a new approach, actors and expectations to the area, mainly the perspective on social crime prevention. An original experience based in this new paradigm has entered the public policy agenda on security in the state of Minas Gerais when formulating its social policy system. Minas Gerais State Policy to Social Crime Prevention was described in this study as a way to highlight its objectives, target audience, structural programmes and transversal actions. Moreover, this study has made an analysis of its process of implementation, in which there were verified variables that revealed its low institution building as well as the absence of adequate institutional conditions to promote a substantive change in the agenda of public security. The paradigm of Citizen Security has entered the system through the process of incrementation and also through the personal mediation of certain strategic players. The paradigms on Social Crime Prevention were not assimilated by the system in which hegemonic groups have made themselves as coalitions in favour of a deeper approach on a punitive agenda. The policy on Social Crime Prevention was institutionalized, but its legitimacy was internal in the process of building its own ceremonies and less on the outside where it was kept as a marginal option. In front of a low institutional building, it can be concluded that in a context of path-dependence, unbalances of power and hostile coalitions to its consolidation, the movement toward gradual changes is the only possible way to evolve.